Pelestarian Gamelan dan Tari Tradisional melalui Program COP sebagai Upaya Pemberdayaan Masyarakat di Desa Dilem - Ke Lomi, Aplonia Nelci (Universitas Muhammadiyah Mataram, 2026)
This community service program was conducted in Dilem Village as part of the Community Outreach Program (COP) 2025. The main objective of the program was to preserve local cultural heritage, particularly traditional gamelan music and dance, as the primary focus of community empowerment, while also implementing several supporting programs in education, environment, and village administration. The implementation method consisted of needs analysis, training and mentoring, cultural workshops, collaborative performances, and monitoring and evaluation involving local communities and COP participants. The results of the program showed increased community participation, improved skills of local youth in playing gamelan and performing traditional dance, and stronger awareness of cultural preservation. In addition, supporting programs, such as educational infrastructure improvements, mural creation, green public space development, foreign culture classes, and administrative assistance, contributed to the community's overall empowerment. This program demonstrates that integrating cultural preservation with various community-based activities can effectively strengthen social engagement and local development.